IPTEKS SISTEM INFORMASI PEMBAYARAN PAJAK KENDARAAN BERMOTOR PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Dalonto, Miswati; Kentey, Sianly Lovely; Tinangon, Jantje J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Badan Pendapatan Daerah Provinsi Sulawesi Utara are moving in taxation sector, especially in Provincial Taxes that is motor vehicle taxation. A good tax payment system needs tax payment information systems that can make it easier for taxpayers to pay the taxes. Motor vehicle tax is one of the Regional Original Revenues, so the office of Badan Pendapatan Daerah Provinsi Sulawesi Utara creates and implements the Info Pajak Kendaraan Sulut application with the purpose  to facilitating  taxpayers to pay the tax, because this application can already provide the motor vehicle tax information in North Sulawesi region that is the amount of  PKB, SWDKLLJ,  and PNBP which are accompanied by a payment code that can be used to pay the motor vehicle tax. With this application Badan Pendapatan  Daerah Provinsi Sulawesi Utara can easily help the taxpayers to make the tax payments because taxes are compulsory and have to be paid for use of the needs of the country and prosperity of the people.Keywords : system information and application, taxes, motor vehicle tax